2021
DOI: 10.3390/cancers13071623
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Checkpoint Inhibitor Treatment in Patients with Advanced Renal or Urothelial Cell Carcinoma and Concomitant Chronic Kidney Disease: A Retrospective Cohort Study

Abstract: Background: Checkpoint inhibitors are a standard of care in the treatment of advanced renal cell carcinoma (RCC) and urothelial carcinoma (UC). Patients with these tumors often suffer from concomitant chronic kidney disease (CKD). Limited data are available on the efficacy and toxicity of checkpoint inhibitors in patients with CKD. Methods: We retrospectively analyzed 126 patients who received checkpoint inhibitors for RCC (n = 85) or UC (n = 41) and analyzed the frequency of treatment- and immune-related adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…In terms of efficacy, all of the present and previously reported cases were well controlled using combination therapy, although the reported cases are likely subject to selection bias. The present and previous case reports are consistent with the efficacy of immune checkpoint inhibitors in patients with chronic kidney disease being similar to that in patients without [2, 8, 9].…”
Section: Discussionsupporting
confidence: 91%
“…In terms of efficacy, all of the present and previously reported cases were well controlled using combination therapy, although the reported cases are likely subject to selection bias. The present and previous case reports are consistent with the efficacy of immune checkpoint inhibitors in patients with chronic kidney disease being similar to that in patients without [2, 8, 9].…”
Section: Discussionsupporting
confidence: 91%
“…Two previous studies of patients with metastatic genitourinary cancers had demonstrated that CKD did not increase irAE risk (one using a cutoff of eGFR < 60 mL/minute/1.73 m 2 , and another using creatinine clearance < 30 mL/minute); our results expand these conclusions to a larger set of cancer types. 37 …”
Section: Discussionmentioning
confidence: 99%